The magic school bus gets eaten : a book about food chains - Relf, Patricia; Cole, Joanna; Bracken, Carolyn; Scholastic Productions (New York : Scholastic, 1996)
A special field trip on the magic school bus allows Ms. Frizzle's class to see how the food chain works in the ocean.
"Based on the animated TV series produced by Scholastic Productions, Inc. Based on The magic school bus books written by Joanna Cole and illustrated by Bruce Degen"--T.p. verso.
2.4
K-3
Keywords: Food chains (Ecology) -- Juvenile literature; Food chains (Ecology); Food chains (Ecology).